PECULIARITIES OF AMOXICILLIN AND CLAVULANIC ACID APPLICATION AMONG CHILDREN, SUFFERING FROM CHRONIC OBSTRUCTION LUNG DISEASES - O.I. Simonova; L.K. Katosova; A.V. Lazareva (Вопросы современной педиатрии, 2007)
The authors review the application peculiarities of augmentin combined antibiotic (amoxicillin + clavulanic acid), analyze its efficacy during the exacerbation of the chronic obstruction bronchopulmonary process among children. They provide indications, contraindications and intake peculiarities of the given medication among children. Key words: amoxicillin, clavulanic acid, chronic obstruction lung diseases, exacerbation, children.